2019
DOI: 10.3389/fpsyg.2019.01471
|View full text |Cite
|
Sign up to set email alerts
|

School Refusal and Absenteeism: Perception of Teacher Behaviors, Psychological Basic Needs, and Academic Achievement

Abstract: School refusal (SR) is a complex problem that may be caused by different risk factors such as individual and contextual factors ( Kearney, 2007 ; Maynard et al., 2018 ; Heyne et al., 2019 ). These mechanisms can be described in the context of self-determination theory (SDT). For these reasons, the purpose of the present study is investigate the relationship between teacher perceived psychological control and support, psychological basic needs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 55 publications
1
29
0
2
Order By: Relevance
“…Controlling teachers seriously threaten their students’ self‐esteem and intrinsic motivation and can induce feelings of shame and anxiety (Soenens et al, ). Several studies found that a perceived atmosphere of controlling teaching was related to low motivational levels to study (Assor, Kaplan, Kanat‐Maymon, & Roth, ), poor school performance (Filippello, Buzzai, Costa, & Sorrenti, ; Vansteenkiste, Zhou, Lens, & Soenens, ), and school engagement (Earl, Taylor, Meijen, & Passfield, ). Furthermore, exposed to psychologically controlling teaching practices, students feel pressured and may even develop a sense of helplessness in regard to the learning activities (De Meyer, Soenens, Aelterman, de Bourdeaudhuij, & Haerens, ; Filippello et al, ).…”
Section: Controlling Versus Autonomy‐supportive Teaching Stylementioning
confidence: 99%
“…Controlling teachers seriously threaten their students’ self‐esteem and intrinsic motivation and can induce feelings of shame and anxiety (Soenens et al, ). Several studies found that a perceived atmosphere of controlling teaching was related to low motivational levels to study (Assor, Kaplan, Kanat‐Maymon, & Roth, ), poor school performance (Filippello, Buzzai, Costa, & Sorrenti, ; Vansteenkiste, Zhou, Lens, & Soenens, ), and school engagement (Earl, Taylor, Meijen, & Passfield, ). Furthermore, exposed to psychologically controlling teaching practices, students feel pressured and may even develop a sense of helplessness in regard to the learning activities (De Meyer, Soenens, Aelterman, de Bourdeaudhuij, & Haerens, ; Filippello et al, ).…”
Section: Controlling Versus Autonomy‐supportive Teaching Stylementioning
confidence: 99%
“…School non-attendance has been linked to numerous deficits, such as cognitive-academic, social and behavioral. Specifically, School Attendance Problems (SAPs) have been linked to poor academic performance, low scores on reading and mathematics tests, grade repetitions and even school dropout (1)(2)(3)(4). Likewise, internalizing and externalizing behavior problems are frequent in adolescents with difficulties attending school, among which we can include anxiety, depression, substance use and pre-criminal behavior (5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a supportive context that encourages autonomy increases the level of student engagement and effectively balances students' needs and their academic activities, promoting the formation of an internal locus of motivation (Reeve et al, 2004;Reeve and Jang, 2006) and persistence even in the face of failure (Aunola et al, 2013). Therefore, a supportive environment strengthens self-realization and can facilitate positive functioning among adolescents within schools (Reeve and Jang, 2006;Filippello et al, 2019a). On the contrary, a thwarting context, characterized by pressure and coercion that makes individuals feel inadequate and emotionally disconnected, favors maladjustment and the development of school HPL (Barber and Harmon, 2002;Soenens et al, 2010;Li et al, 2016;Filippello et al, 2020).…”
Section: Introductionmentioning
confidence: 99%